A perspective and a way to explain competence in the context of tasks performance - Basoredo, Carmelo (Anales de Psicología / Annals of Psychology, 2011)
The aim of this article is to carry out a new interpretation of the concept of Professional Competence, in the light of Tasks Performance Theories with the possibility that this new interpretation can be applied generally to any of the fields where the concept of competence is usually applied. For that purpose, after revising some of the main previous perspectives and orientations, a definition of Competence is chosen as a work style or effective performance, making reference to a rule that represents the elements of content and the criteria to justify and defend this proposal. At the same time, different methodologies to identify Competences are analyzed and some of their advantages and drawbacks are given. However, the matter of classification is avoided since it is considered that any typology of competences is more closely related to its specific uses than with the definition of the concept.